2018
DOI: 10.1101/313452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved glycine harboring disease-associated mutations is required for slow deactivation and high Ca2+ permeability in NMDA receptors

Abstract: A variety of de novo and inherited missense mutations associated with neurological disorders are found in the NMDA receptor M4 transmembrane helices, which are peripheral to the pore domain in eukaryotic ionotropic glutamate receptors. Subsets of these mutations affect receptor gating with dramatic effects, including in one instance halting it, occurring at a conserved glycine near the extracellular end of M4. Functional experiments and molecular dynamic simulations of constructs with and without substitutions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Most NMDARs in the cortex and hippocampus contain GluN2B, with levels peaking during the third postnatal week. A variety of strategies have been used to examine whether mutant GluN2B is properly trafficked, including surface immunolabeling of unpermeabilized (or mildly permeabilized) cells (Liu et al, 2017;Sceniak et al, 2019;Santos-Gómez et al, 2021), surface biotinylation-based approaches (Ogden et al, 2017), and fluorescent/luminescent/colorimetric reporter methods (Swanger et al, 2016;Amin et al, 2018;Li et al, 2019;Kellner et al, 2021). These studies showed that some variants produce GluN2B that is not trafficked to the cell surface, while others are trafficked less efficiently than or equivalent to wildtype.…”
Section: Analysis Of Mutant Subunit Trafficking and Currents In The A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Most NMDARs in the cortex and hippocampus contain GluN2B, with levels peaking during the third postnatal week. A variety of strategies have been used to examine whether mutant GluN2B is properly trafficked, including surface immunolabeling of unpermeabilized (or mildly permeabilized) cells (Liu et al, 2017;Sceniak et al, 2019;Santos-Gómez et al, 2021), surface biotinylation-based approaches (Ogden et al, 2017), and fluorescent/luminescent/colorimetric reporter methods (Swanger et al, 2016;Amin et al, 2018;Li et al, 2019;Kellner et al, 2021). These studies showed that some variants produce GluN2B that is not trafficked to the cell surface, while others are trafficked less efficiently than or equivalent to wildtype.…”
Section: Analysis Of Mutant Subunit Trafficking and Currents In The A...mentioning
confidence: 99%
“…Receptors that are never delivered to the cell surface cannot function as plasma membrane receptors and ion channels; for receptors that reach the cell surface, it is necessary to measure their channel properties directly. Electrophysiology and calcium imaging have been used to evaluate channel function (Swanger et al, 2016;Ogden et al, 2017;Amin et al, 2018;Fedele et al, 2018;Vyklicky et al, 2018;Li et al, 2019;Sceniak et al, 2019;Shin et al, 2020;Kellner et al, 2021;Santos-Gómez et al, 2021;Elmasri et al, 2022). Some mutants form NMDARs possessing channels that are completely non-functional.…”
Section: Analysis Of Mutant Subunit Trafficking and Currents In The A...mentioning
confidence: 99%
See 1 more Smart Citation